PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN TATA BAHASA SECARA ONLINE DI PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Angga Safitri; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: During the current covid-19 pandemic, teaching and learning activities turned into online learning. But online learning is experiencing many obstacles. Inadequate infrastructure and learning goals that are not conveyed properly are one of the obstacles felt by lecturers and students.The aim of the study was to find out how students perceive online grammar learning using descriptive quantitative approach methods.Data collection in this study used non-tests in the form of kuisoner with 68 respondents as the population.From this study obtained the results that the perception of students to the aspect of planning is in the good category with a percentage of 79.5%, the implementation aspect is in the good category with a percentage of 70.0% and the evaluation aspect is in the category of less good with a percentage of 66.3%.Key Words : Perception, Grammar, Online Learning.